A Study of Compressive Strength and Density of Aerated Concrete - Kraiwood Kiattikomol; Aikachai Sae Lim; Anek Siripanichgorn (Universitas Gadjah Mada, 1988)
A Study of Compressive Strength and Density of Aerated Concrete